2018
DOI: 10.1002/bdr2.1148
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to high doses of selenium in the first trimester of pregnancy: Case report and brief literature review

Abstract: This is the first case of severe chronic selenium intoxication during the first trimester of pregnancy. In the present case, no consequences of congenital defects or pregnancy complications occurred. However, since vitamins, minerals, and food supplements may be harmful and prescription errors occur, obstetricians should avoid prescribing supplements in the absence of maternal deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In addition, studies which reported such signs and symptoms at plasma/serum selenium concentrations above 850 μg/L were also excluded, under the conservative assumption that a daily intake of 850 μg is equivalent to a plasma or serum selenium concentration of 850 μg/L (the prediction equation described in Section 3.3.2 is not applicable at these levels). As a result, eight publications on case reports or case series of chronic selenium poisoning were not further assessed (No authors listed, 1984;Sutter et al, 2008;Dosary et al, 2009;MacFarquhar et al, 2010;Aldosary et al, 2012;Morris and Crane, 2013;Razmi et al, 2017;D'Oria et al, 2018). In addition, the study by Garc ía-Esquinas et al (2021) was not considered because it only reported on 'weakness', without other signs and symptoms of selenium toxicity (Annex E).…”
Section: Additional Data Identifiedmentioning
confidence: 99%
“…In addition, studies which reported such signs and symptoms at plasma/serum selenium concentrations above 850 μg/L were also excluded, under the conservative assumption that a daily intake of 850 μg is equivalent to a plasma or serum selenium concentration of 850 μg/L (the prediction equation described in Section 3.3.2 is not applicable at these levels). As a result, eight publications on case reports or case series of chronic selenium poisoning were not further assessed (No authors listed, 1984;Sutter et al, 2008;Dosary et al, 2009;MacFarquhar et al, 2010;Aldosary et al, 2012;Morris and Crane, 2013;Razmi et al, 2017;D'Oria et al, 2018). In addition, the study by Garc ía-Esquinas et al (2021) was not considered because it only reported on 'weakness', without other signs and symptoms of selenium toxicity (Annex E).…”
Section: Additional Data Identifiedmentioning
confidence: 99%
“…However, humans seem to be relatively robust to acute Se intoxication, as most of the symptoms described from a daily intake of pills containing 22-32 mg of Se per serving were reversible, and luckily, no fatal course occurred [177]. Even more surprising are sporadic case reports, e.g., from a pregnant mother taking 200 mg of Se per day (i.e., 1000-fold higher than the commonly accepted maximal dosage used in clinical trials) during gestational weeks 7 to 12 [178]. The women lost hair and fingernails, as expected from severe selenosis, but surprisingly gave birth at term to a healthy child [178].…”
Section: Potential Toxicity Of Supplemental Sementioning
confidence: 99%
“…Even more surprising are sporadic case reports, e.g., from a pregnant mother taking 200 mg of Se per day (i.e., 1000-fold higher than the commonly accepted maximal dosage used in clinical trials) during gestational weeks 7 to 12 [178]. The women lost hair and fingernails, as expected from severe selenosis, but surprisingly gave birth at term to a healthy child [178]. These examples indicate that supplemental Se can be toxic and even fatal, irrespective of the underlying motivation for health-support or suicidal intention [179].…”
Section: Potential Toxicity Of Supplemental Sementioning
confidence: 99%
“…Conversely, Se toxicity (selenosis) can occur with acute or chronic ingestion of excess Se. The most common adverse health impacts of selenosis are alopecia and nail brittleness and loss (30) , as well as gastrointestinal disturbances, skin rash, garlic breath odor, fatigue, irritability, and eventually nervous system abnormalities and paresthesia (31,32) . Mechanisms of Se toxicity remain unconfirmed but selenosis likely occurs as a result of oxidative stress generation and consequent disruptions of cellular and mitochondrial function (33,34) .…”
Section: Dietary Reference Values and Safe Upper Limitsmentioning
confidence: 99%